LPIC-1: Linux Professional Institute Certification. Study guide - Smith, Roderick W. (Roderick W. Smith) (Editorial Wiley Publishing, 2005)
horough LPICâ1 exam prep, with complete coverage and bonusstudy tools LPICâ1Study Guide is your comprehensive source for thepopular Linux Professional Institute Certification Level 1 exam,fully updated to reflect the changes to the latest version of theexam. With 100% coverage of objectives for both LPI 101 and LPI102, this book provides clear and concise information on all Linuxadministration topics and practical examples drawn from realâworldexperience. Authoritative coverage of key exam topics includes GNUand UNIX commands, devices, file systems, file system hierarchy,user interfaces, and much more, providing complete exam prep forthe LPICâ1 candidate. Get access to invaluable study tools,including bonus practice exams, electronic flashcards, and asearchable PDF of key terms featured on the exam.Linux is viewed by many companies and organizations as anexcellent, lowâcost, secure alternative to expensive operatingsystems, such as Microsoft Windows. The LPICâ1 tests a candidate?sunderstanding and familiarity with the Linux Kernel. This bookprovides comprehensive preparation and review, helping readers facethe exam with confidence. Review the system architecture, Linux installation, and packagemanagement Understand shells, scripting, and data management morecompletely Practice administrative tasks and essential systemservices Brush up on networking fundamentals and security issuesAs the Linux server market share continue to grow, so too doesthe demand for qualified and certified Linux administrators.Certification holders must recertify every five years, but LPIrecommends recertifying every two years to stay fully up to datewith new technologies and best practices. As exam day approaches,LPICâ1Study Guide is the one source you will want by yourside.